ANALISIS PERBANDINGAN HUKUM TENTANG PEMUNGUTAN ZAKAT DAN PAJAK DALAM SISTEM PERPAJAKAN NASIONAL: SIGIT BUDIARTO IYABU - IYABU, SIGIT BUDIARTO (Ganec Swara, 2025)
Zakat functions as a social instrument that aims to distribute wealth to those in need, while taxes function to finance state development. In the legal framework, zakat is regulated by Law No. 23 Year 2011 on Zakat Management and can be used as an income tax deduction in accordance with the provisions in Law No. 36 Year 2008 on Income Tax. This policy provides flexibility for muzaki to reduce their tax burden through legitimate zakat payment, which is regulated in Government Regulation No. 60 Year 2010. Nonetheless, the implementation of this provision still faces various challenges, including low public literacy regarding the benefits of zakat as a tax deduction and lack of socialization from relevant authorities. Data shows that despite the considerable potential of zakat, only a small portion of muzaki optimally utilize this provision. In this analysis, a comparison between zakat and tax collection mechanisms will be discussed, as well as their impact on state revenue and public welfare. This research aims to explore the relationship between these two obligations and seek solutions to improve the effectiveness of zakat management in the context of national taxation. By understanding the differences and similarities between zakat and tax, it is hoped that a better synergy can be found for the welfare of the people and the development of the country.